2023
DOI: 10.1038/s41598-023-29082-1
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to nonnative-accented speech reduces listening effort and improves social judgments of the speaker

Abstract: Prior research has revealed a native-accent advantage, whereby nonnative-accented speech is more difficult to process than native-accented speech. Nonnative-accented speakers also experience more negative social judgments. In the current study, we asked three questions. First, does exposure to nonnative-accented speech increase speech intelligibility or decrease listening effort, thereby narrowing the native-accent advantage? Second, does lower intelligibility or higher listening effort contribute to listeners… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Still, to generalize these findings, further studies are needed to systematically examine a broader range of adverse conditions and their effect on the degree of effort experienced. Additionally, recent studies on monolinguals indicate that exposure to adverse listening conditions can lead to a rapid decrease in listening effort due to an adaptation process (Brown et al, 2020;Rovetti et al, 2023). Therefore, it is crucial for future studies to investigate whether a similar adaptation process exists among bilingual listeners and to what extent it can compensate for the increased effort observed in their nondominant language.…”
Section: Listening Effort Combining Behavioral and Subjective Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, to generalize these findings, further studies are needed to systematically examine a broader range of adverse conditions and their effect on the degree of effort experienced. Additionally, recent studies on monolinguals indicate that exposure to adverse listening conditions can lead to a rapid decrease in listening effort due to an adaptation process (Brown et al, 2020;Rovetti et al, 2023). Therefore, it is crucial for future studies to investigate whether a similar adaptation process exists among bilingual listeners and to what extent it can compensate for the increased effort observed in their nondominant language.…”
Section: Listening Effort Combining Behavioral and Subjective Measuresmentioning
confidence: 99%
“…For example, changes in cardiac responses (e.g., Mackersie & Calderon-Moultrie, 2016; Mackersie & Cones, 2011; Seeman & Sims, 2015), hormonal activity (e.g., Jahncke & Halin, 2012), or skin conductance responses (e.g., Mackersie & Calderon-Moultrie, 2016; Mackersie & Cones, 2011; Seeman & Sims, 2015), were attributed to changes in effort. In addition, changes in the synchronization of alpha and theta oscillations during electroencephalogram (EEG) recordings (Deng et al, 2019; Miles et al, 2017; Obleser et al, 2012; Wisniewski, 2017; Wisniewski et al, 2018), changes in the topography, latency, or amplitude of event-related potentials (ERPs) (e.g., Bertoli & Bodmer, 2016; Kyong et al, 2020; Obleser & Kotz, 2011; Ullsperger et al, 1988), or recruitment of additional brain areas in neuroimaging studies (e.g., Eckert et al, 2016; Peelle, 2018; White & Langdon, 2021; Wild et al, 2012) were found to be associated with the difficulty of the task and were interpreted to reflect changes in effort.…”
Section: Introductionmentioning
confidence: 99%